MINERALOGY AND GEOCHEMISTRY OF DIBDIBBA Sandstone Formation BEARING FELDSPAR IN ZUBAIR AND SAFWAN AREA’ S , SOUTHERN IRAQ - AL- Khafaji, S.; AL-Shmmary, T.; AL- Najar, N. (Iraqi Journal of Science, 2024)
Twenty nine sand samples bearing feldspar from Dibdibba sands formation, southern Iraq were studied mineralogically and geochemically in two different Locations: Safwan and Zubair areas, to evaluated their content of feldspar and Quartz .